Negotiating CACREP Accreditation Practices, Religious Diversity, and Sexual Orientation Diversity: A Rejoinder to Sells and Hagedorn. (9th June 2016) - Smith, Lance C.; Okech, Jane E. Atieno
Abstract : The authors write a rejoinder to Sells and Hagedorn's (2016 ) article, "CACREP Accreditation, Ethics, and the Affirmation of Both Religious and Sexual Identities: A Response to Smith and Okech, " which supports Smith and Okech's (2016 ) assertion that a dialogue examining the Council for Accreditation of Counseling and Related Educational Programs' accreditation practices pertaining to counseling programs in institutions that disaffirm/disallow diverse sexual orientation is germane. The authors articulate the common ground they share with Sells and Hagedorn while also highlighting areas of dissension.